Fiqh Studies and Critical Thinking in Pesantren-Based Islamic Education: Revisiting UNESCO’s Four Pillars - Muhammad Munir; Faizetul Ukhrawiyah (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study is important because it addresses the growing need for critical thinking in Islamic boarding school-based education, which is often considered to emphasize traditionalism and rote learning rather than analytical engagement. Despite this perception, the study of fiqh, the traditional Islamic discourse on problem solving, contains dialogical and analytical elements that have not been sufficiently researched in the context of contemporary education. Using a qualitative research approach based on library research with a Systematic Literature Review (SLR) design, this study examines literature from 2010 to 2024 sourced from Scopus, Web of Science, and Google Scholar. The review identified three main themes: (1) the pedagogical structure of fiqh studies, (2) its cognitive impact on students' critical reasoning, and (3) the integration of pesantren traditions with higher education pedagogy. The findings show that fiqh studies offer a culturally rooted, reflective, and problem-oriented model of inquiry that encourages students to engage in argumentation, ethical deliberation, and collaborative learning. This review contributes to the ongoing debate on the decolonization of education and offers insights into how traditional Islamic epistemology can contribute to global educational reform.